A study of the scientific information needs and literature use of researches at the Aquaculture Department, Southeast Asian Fisheries Development Center, Tigbauan, Iloilo, Philippines - Orejana, Rebecca Dacanay, 1948-
Data were gathered by means of a questionnaire submitted to a group of 156 researchers in the disciplines of aquaculture and fisheries. Analysis of 623 references cited in 76 published and unpublished research reports and research papers prepared by SEAFDEC international trainees and researchers, and analysis of statistics of library loans supplemented the data obtained from the answers of 109 respondents.
Findings show that the type of library instruction received by majority of the respondents is the informal or incidental type of instruction. At least twelve percent of them stated that they had received no significant library instruction in college or graduate school. Only 31 percent of them, in general, can read and understand at least one foreign language except English. Only 17 percent of their working time is allocated to literature search.
Majority of the respondents prefer to use documentary, primary sources of scientific information. At least 44 percent of them are not fully aware of the availability of information services offered by the SEAFDEC Library. The researchers assigned in substations of SEAFDEC are encountering difficulties in their search for scientific information. Majority of the respondents prefer to do literature searches themselves.
Many of the respondents did not consider their literature searches successful because of certain inadequacies in their library facilities and resources, and the lack of sufficient time for library work. However, majority of the graduate students considered the SEAFDEC Library facilities very useful for research.
Salient topics discussed in the study pertain to the information-seeking behavior of the respondents, the type and scope of scientific information needed by them, the purposes or objectives which motivate them to conduct literature searches, and the prevailing role of the "invisible college," colleagues and librarians in the dissemination of scientific information.
The scientific information-seeking behavior of the respondents is motivated by certain objectives. The objective to provide specific information needed for work in progress was found to be the main motivation.
The scope and type of scientific information needed by the respondents is multi-disciplinary in nature and intersect wide subject areas, with Aquaculture heading the list, followed by Biology.
The vital role of the informal sources of information in the dissemination of scientific information such as the "invisible colege" is not yet fully recognized by the respondents who tend to be more self-reliant in their search for scientific information.
This study attempts to contribute towards the attainment of efficient dissemination and effective utilization of scientific information, particularly in the fields of aquatic sciences and fisheries. It examined and evaluated the current scientific information needs and literature use of the researchers at the Aquaculture Department, Southeast Asian Fisheries Development Center, Tigbauan, Iloilo, Philippines.
To adequately provide for the scientific information needs of the growing research community, the further improvement and expansion of the SEAFDEC Library and information system complemented by the acceleration of the SEAFDEC Library Staff Development Program is recommended.
Mimeographed.
Thesis (M.L.S)--University of the Philippines, Diliman
Keywords: Aquaculture--Information services--Philippines.; Fisheries--Information services--Philippines.; Southeast Asian Fisheries Development Center